Mycotoxin Exposure and Related Diseases - Viegas, Susana (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Mycotoxins are considered the most frequently occurring natural contaminants in human and animal diets. Considering their potential toxic and carcinogenic effects, mycotoxin exposure assessment has particular importance in the context of health risk assessment. The magnitude of a given exposure allows the derivation of the associated risk and the potential for the establishment of a disease. Although food ingestion is considered a major route of human exposure to mycotoxins, other contexts may also result in exposure, such as specific occupational environments where exposure to organic dust also occurs due to the handling of organic materials. Animals could be exposed to mycotoxins through consumption of contaminated feed, subsequently entering in the food chain and thus constituting a source of exposure to humans. Human biomonitoring is considered a new frontier for the establishment of the human internal exposure to mycotoxins. Although several studies have summarized the potential outcomes associated with mycotoxin exposure, major gaps in data remain in recognizing the mycotoxins that are the cause of diseases. This book contributes provides research that supports the anticipation of potential consequences of the exposure of humans and animals to mycotoxins, future risk assessments, and the establishment of preventive measures.